European Parliament Election Study 2014 - Oscarsson, Henrik; Berg, Linda; Hedberg, Per (University of Gothenburg, 2022)
The European Parliament Election Study 2014 was conducted in collaboration between the Department of Political Science in Gothenburg and Statistics Sweden (SCB). This collaboration has covered all of the parliamentary elections, referendums and elections to the European Parliament since 1956.

In 2014 the Swedish National Election Studies (SNES) team changed the primary mode of the study from face to face to a 24
page mail-back paper survey. One of the main reasons for the mode change was the ever increasing
costs of preforming face to face interviews. Another reason was to combat the trend of declining
response rate and to ensure large enough (n) in the study. As a result the sample size was doubled to
5400 individuals.

Europaparlamentsvalundersökningen 2014 genomfördes i samarbete mellan Statsvetenskapliga institutionen, Göteborgs universitet och Statistiska centralbyrån (SCB). Samarbetet har pågått vid samtliga ordinarie riksdagsval, folkomröstningar och Europaparlamentsval sedan 1956.

I 2014 års undersökning ändrades den primära insamlingsmetoden från personlig intervju till pappersenkät. En av huvudanledningarna till att man ändrade metod var en ökad kostnad att genomföra intervjuerna. En annan anledning var den sjunkande svarsfrekvensen och att man ville säkra ett så stort underlag som möjligt. Som ett resultat av detta dubblerades urvalet till 5400 individer.
Europaparlamentsvalundersökning 2014
Keywords: elections; val; politics; politik; public opinion; allmän opinion; european union; europeiska unionen; electoral systems; valsystem; political leaders; politiska ledare; politicians; politiker; election campaigns; valkampanjer; electoral issues; valfrågor; internal politics; inrikespolitik; free will; fri vilja; european parliament elections; europaparlamentsval; european parliament; europaparlamentet; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Government, political systems and organisations; Regering, politiska system och organisationer; International politics and organisations; Internationell politik och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap